Kesejahteraan Sosial Marbot Masjid Dalam Menjaga Kebersihan Masjid di Kelurahan Sayurmatinggi - Ahmad Suryadi; Sahrul (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
The role of mosque custodians (marbot) is crucial in maintaining the cleanliness and security of the mosque environment. Despite its importance, the social welfare of marbots is often suboptimal, particularly in terms of salary. This study explores the social welfare of marbots in managing mosque cleanliness, with a focus on salary, work facilities, and recognition of their contributions. The research was conducted at Ar-Rahman Grand Mosque in Sayurmatinggi Village using descriptive techniques and a qualitative approach. Data were collected through observation, interviews, and documentation in February 2024. Data triangulation was employed to ensure the reliability and validity of the findings. The results indicate that the social welfare of marbots in managing mosque cleanliness is still suboptimal, especially concerning salaries. The role of marbots extends beyond physical cleanliness to include significant social interactions with congregants, contributing to a positive atmosphere in the mosque. Enhancing the social welfare of marbots through better salaries, adequate work facilities, and recognition of their contributions is essential for increasing their motivation and commitment to maintaining mosque cleanliness